Inverted U-shaped relationship between education and family health: The urban-rural gap in Chinese dual society - Jia, Changli; Long, Yanwen; Luo, Xiaoxia; Li, Xiao; Zuo, Wenjing; Wu, Yibo (Frontiers in Public Health, 2023)
Introduction The Healthy China Initiative emphasizes family health. Education is an upstream determinant of health, which can both achieve upward mobility and cause class solidification. Methods Using nationwide large-scale data collected in 2021, the present study explored the relationship between education and family health in the urban-rural dual society via Oaxaca-Blinder decomposition and propensity score matching. Results Our data revealed disparities in family health, educational attainment, household income, healthcare coverage, and job type between urban and rural China. An inverted U-shaped relationship existed between increasing years of education and family health. The upper limit was 17.1 years for urban residents and 13.7 years for rural residents, with limited health benefits from higher education obtained by rural residents. Mediated by work-family conflict, highly-educated people received gradually diminishing health returns. The results of the Oaxaca-Blinder decomposition showed that 25.8% of the urban-rural gap in family health could be explained by the disparity in education. Urban residents could translate cultural capital and economic capital into health capital to a greater extent. After propensity score matching, a robust, inverted U-shaped relationship was found between education and family health. The inverted U-shaped relationship was found to replace family health with self-rated health and quality of life. Discussion Family-centered public health and education programs, policies, and goals should be developed to break urban-rural dual structure barriers and advance social equity in China.